Dental non-metric traits in a pre-conquest sample "calchaquí" from Argentina, South America - Bollini, Gabriel A. (2009)
The present study was carried out with a Calchaquí human Pre-Conquest sample from Northwest of Argentina, with the aim of exploring the dental morphology patterns in this population. This study was carried out by means of a macroscopic analysis in permanent dentitions of 7 skulls. 40 dental non-mtetric traits were recorded using the ASU Dental Anthropology System. Percentages >70% was found only in 4 traits. Calchaquí sample studied here is near to these values in shovel shape expression, but the results of this study suggest that a Sinodont pattern is no clear for this sample. To conclude, the present investigation provides additional, insightful elements for a description of biological factors in the process of dental morphologic diversification associated to regional and temporal ranges in this region of Argentina.